If h(x) = (fog) (x) and h(x) = 4 square root x+7, find g(x) if f(x) = 4 square root x+ 1

Answers

Answer 1

Answer:

[tex]g(x)=x+6[/tex] is the answer

given

[tex]h(x)=4\sqrt{x+7}[/tex] and [tex]f(x)=4\sqrt{x+1}[/tex].

Step-by-step explanation:

[tex]h(x)=(f \circ g)(x)[/tex]

[tex]h(x)=f(g(x))[/tex]

Inputting the given function for h(x)  into the above:

[tex]4\sqrt{x+7}=f(g(x))[/tex]

Now we are plugging in g(x) for x in the expression for f which is [tex]4\sqrt{x+1}[/tex] which gives us [tex]4\sqrt{g(x)+1}[/tex]:

[tex]4\sqrt{x+7}=4\sqrt{g(x)+1}[/tex]

We want to solve this for g(x).

If you don't like the looks of g(x) (if you think it is too daunting to look at), replace it with u and solve for u.

[tex]4\sqrt{x+7}=4\sqrt{u+1}[/tex]

Divide both sides by 4:

[tex]\sqrt{x+7}=\sqrt{u+1}[/tex]

Square both sides:

[tex]x+7=u+1[/tex]

Subtract 1 on both sides:

[tex]x+7-1=u[/tex]

Simplify left hand side:

[tex]x+6=u[/tex]

[tex]u=x+6[/tex]

Remember u was g(x) so you just found g(x) so congratulations.

[tex]g(x)=x+6[/tex].

Let's check it:

[tex](f \circ g)(x)[/tex]

[tex]f(g(x))[/tex]

[tex]f(x+6)[/tex] I replace g(x) with x+6 since g(x)=x+6.

[tex]4\sqrt{(x+6)+1}[/tex] I replace x in f with (x+6).

[tex]4\sqrt{x+6+1}[/tex]

[tex]4\sqrt{x+7}[/tex]

[tex]h(x)[/tex]

The check is done. We have that [tex](f \circ g)(x)=h(x)[/tex].


Related Questions

Is 24/40= 4/8 true proportion?

Answers

Answer:

No, that is not the true proportion.

Step-by-step explanation:

40 divided by 8 is 5. 5 multiplied by 4 is 20. Therefore, the true proportion would be 20/40 = 4/8.

If ELF is congruent to GJH, EF=12 and LF=7.8 find IJ. Round answer to the hundredths place. A. 4.78 B 5.62 C 4.98 D 5.07

Answers

EF = 12

KF = 6

LF = 7.8

LK = sqrt(7.8^2-6^2) = 4.98

IJ = LK

Answer with explanation:

→ΔELF ≅ Δ GHJ-------[Given]

→EF=GH----------[CPCT]

→GJ=FL-------[CPCT]

Let , O be the center of the circle.

→ EK=KF--------[Perpendicular from the center to the chord bisects the chord.]

→GI=IH------[Reason same as Above]

→→EK=GI, KF=HI

→→OJ=OL

→OK=KI

→OJ-OK=OL-KI

→LK=IJ

⇒→Δ LKF ≅ Δ JIG-------[SAS]

Now, In Δ LKF, By Pythagorean Theorem

 →(LF)²=(LK)²+(KF)²

→(7.8)²=(LK)²+(6)²

→60.84-36=(LK)²

→24.84=(LK)²

LK=4.98

→→LK=IJ=4.98

Option C:→4.98

HELP!!!! PLEASE need help now its an emergency.

Answers

Answer:

121,6

Step-by-step explanation:

Since the only difference between the triangles are the letters and a few missing numbers, just replace the letters to get your answer. A and D are the same B and E are the same and C and F are the same. So the measurement of angle A is 121 degrees and the length of AB is 6

Rip van Winkle fell asleep for a very long time. When he fell asleep, his beard was 8 millimeters long, and each passing week it grew 2 additional millimeters.
Graph the length of Rip van Winkle's beard (in millimeters) as a function of time (in weeks).

Please help me to understand how to graph this problem.

Answers

A function that models the situation is f(x) = 2x + 8.

A graph of the length of Rip van Winkle's beard (in millimeters) as a function of time (in weeks) is shown in the picture below.

In Mathematics, the slope-intercept form of the equation of a straight line refers to the general equation of a linear function and it is represented by this mathematical equation;

y = mx + b

where:

m represents the slope.x and y are the points.b represents the y-intercept or initial value.

Since Rip van Winkle's beard was 8 millimeters long when he fell asleep, and each passing week it grew 2 additional millimeters, we can logically deduce the following parameters;

slope, m = 2.

initial value or y-intercept, b = 8.

In this context, an equation for the function that relates the length of his beard (in millimeters) to time (in weeks) can be written as follows;

y = mx + b

f(x) = 2x + 8

Subtract. 5x^2-5x+1-(2x^2+9x-6)

Answers

Hello!

The answer is:

[tex]3x^{2} -14x+7[/tex]

Why?

To solve the problem we need to add/subtract like terms. We need to remember that like terms are the terms that share the same variable and the same exponent.

For example, we have:

[tex]x^{2} +2x+3x=x^{2} +(2x+3x)=x^{2}+5x[/tex]

We have that we were able to add just the terms that were sharing the same variable and exponenr (x for this case).

So, we are given the expression:

[tex]5x^2-5x+1-(2x^2+9x-6)=5x^{2}-2x^{2}-5x-9x+1-(-6)\\\\(5x^{2}-2x^{2})+(-5x-9x)+(1-(-6))=3x^{2}-14x+7[/tex]

Hence, the answer is:

[tex]3x^{2} -14x+7[/tex]

Have a nice day!

simplify the following fraction (9/16/1/4)-1/5

Answers

Answer: [tex]\frac{41}{20}[/tex]

Step-by-step explanation:

The first step is to make the division of the fractions [tex]\frac{9}{16}[/tex] and

[tex]\frac{1}{4}[/tex]. To do this, you can flip the fraction [tex]\frac{1}{4}[/tex] over and multiply the numerators and the denominators of the fractions. Then:

[tex](\frac{\frac{9}{16}}{\frac{1}{4}})-\frac{1}{5}=(\frac{9}{16}*4)-\frac{1}{5}=\frac{36}{16}-\frac{1}{5}[/tex]

Reduce the fraction [tex]\frac{36}{16}[/tex]:

 [tex]=\frac{9}{4}-\frac{1}{5}[/tex]

Now you can make the subtraction:  in this case the Least Common Denominator (LCD) will be the multiplication of the denominators.   Divide each denominator by the LCD and multiply this quotient by the corresponding numerator and then subtract the products. Therefore you get:

[tex]=\frac{45-4}{20}=\frac{41}{20}[/tex]

Follow the steps and finish the solution.
7(x-3) = 28
Distributive property
7x-21 = 28
Addition property of equality
7x = 49
Division property of equality
X
=
What is the value of x?
07
O 42
O 56
Mark this and return
Save and Exit
Save and Exit
Next
Next
Submit

Answers

Answer:

x=7

Step-by-step explanation:

7(x-3) = 28

Distributive property

7x-21 = 28

Addition property of equality

7x = 49

Division property of equality

7x/7 = 49/7

x = 7

The value of x is 7 ..

Answer:

7

Step-by-step explanation:

Rodney is given two linear equations: x – y = 11 and 2x + y = 19. What value of x should he get as a solution for this system of linear equations

Answers

Answer:

x = 10

Step-by-step explanation:

Given the 2 equations

x - y = 11 → (1)

2x + y = 19 → (2)

Adding the 2 equations term by term eliminates the term in y, that is

(x + 2x) + (- y + y) = (11 + 19), simplifying gives

3x = 30 ( divide both sides by 3 )

x = 10

Answer:

x = 10

Step-by-step explanation:

We know that Rodney is given the following two linear equations and we are to find the value of x at which he would get a solution for this system of linear equations:

[tex] x - y = 1 1 [/tex] - (1)

[tex] 2 x + y = 1 9 [/tex] - (2)

From (1):

[tex]x=11+y[/tex]

Substituting this value of x in (2):

[tex]2(11+y)+y=19[/tex]

[tex]22+2y+y=19[/tex]

[tex]3y=19-22[/tex]

[tex]y=-\frac{3}{3}[/tex]

[tex]y=-1[/tex]

Substituting this value of y in (1) to find x:

[tex]x=11+(-1)[/tex]

x = 10

f(x) = -x^3 + 3x^2 + x - 3 Using the end behavior of f(x), determine the graph of the function

Answers

Answer:

Here, the given function,

[tex]f(x) = -x^3 + 3x^2 + x - 3[/tex]

Since, the leading coefficient is negative, and degree is odd,

Thus, the end behaviour of the function is,

[tex]f(x)\rightarrow \infty\text{ as }x\rightarrow -\infty[/tex]

[tex]f(x)\rightarrow -\infty\text{ as }x\rightarrow \infty[/tex]

Therefore, the graph rises to the left and falls to the right.

Now, when f(x) = 0

[tex]-x^3+3x^2+x-3=0[/tex]

[tex]\implies -(x-3)(x-1)(x+1)=0[/tex]

[tex]\implies x=3, 1, -1[/tex]

That is, graph intercepts the x-axis at (3, 0), (1, 0) and (-1, 0).

When x = 0,

[tex]f(x) = - 3[/tex]

That is, graph intersects the y-axis at ( 0, -3),

Also, for 0 > x > -1 , f(x) is decreasing,

For 2.55 > x > 0, f(x) is increasing,

For 3 > x > 2.55, f(x) is decreasing,

Hence, by the above explanation we can plot the graph of the function ( shown below )

Answer:w

Step-by-step explanation: it should be w i got it on plato

how do I solve this: 9b less than 40

Answers

Answer:

b < 4.44

Step-by-step explanation:

This is an inequality.

The sign for 'less than' is '< '

Write 9b less than 40 in inequality form.

9b < 40 (Take 9 on the other side of the inequality and divide it by 40)

b < 40/9

b < 4.44

!!

Alex and his father took a taxi cab that charges $2.60 per mile plus $1.50 for each passenger, and they paid a total of $18.60. Alex wrote the equation 18.60=2.60b+3 for this situation and found b=6. Which statement is true about the solution b=6?

Answers

Answer:

The solution b=6 tells us that Alex and his father traveled 6 miles on the taxi

Step-by-step explanation:

Given

18.60=2.60b+3

Here 18.60 is the total amount paid, 2.60 is the rate per mile and 3 is the charges for two passengers.

The solution b=6 tells us that Alex and his father traveled 6 miles on the taxi i.e. b represents miles ..

the answer is: the solution b = 6 gives the number of miles the taxi traveled.

i just did the workbook :)

using the rate of Rs. 124.40 per using US dollar, find the US dollar for Rs. 158610.​

Answers

Answer:

1275 USD

Step-by-step explanation:

124.40 Rs -----> 1 USD

158610 Rs -----> x USD

124.40x=158610

×=158610/124.40

x=1275 USD

1.
1400
Simplify: -
Show your work.

Answers

Answer:

1400

Step-by-step explanation:

Nothing can be done further. If I saw the rest of the question, I would be capable of assisting you.

I am joyous to assist you.

PLZ HELP, WILL GIVE BRAINLIEST
What is the value of x?



A.
73°
B.
45°
C.
35°
D.
25°

Answers

Answer:

x = 35

Step-by-step explanation:

The sum of the 3 angles in a triangle = 180°

Subtract the sum of the 2 base angles from 180 for angle at vertex

vertex = 180° - (73 + 51)° = 180° - 124° = 56°

The vertex angle is composed of x and 21, so

x + 21 = 56 ( subtract 21 from both sides )

x = 35

Select the correct answer from each drop-down menu. The base of pyramid A is a rectangle with a length of 10 meters and a width of 20 meters. The base of pyramid B is a square with 10-meter sides. The heights of the pyramids are the same. The volume of pyramid A is the volume of pyramid B. If the height of pyramid B increases to twice that of pyramid A, the new volume of pyramid B is the volume of pyramid A.

Answers

Step-by-step explanation:

The formula of a volume of a pyramid:

[tex]V=\dfrac{1}{3}BH[/tex]

B - base area

H - height

H - height of pyramids

Pyramid A:

[tex]B=(10)(2)=200\ m^2[/tex]

[tex]V_A=\dfrac{1}{3}(200)H=\dfrac{200}{3}H\ m^3[/tex]

Pyramid B:

[tex]B=10^2=100\ m^2[/tex]

[tex]V_B=\dfraC{1}{3}(100)H=\dfrac{100}{3}H\ m^3[/tex]

[tex]V_A>V_B\\\\V_A=2V_B[/tex]

The volume of the pyramid A is twice as large as the volume of the pyramid B.

The new height of pyramid B: 2H

The new volume:

[tex]V_{B'}=\dfrac{1}{3}(100)(2H)=\dfrac{200}{3}H\ m^3[/tex]

The volume of the pyramid A is equal to the volume of the pyramid B.

To compare the volumes of the two pyramids, we first need to calculate the volume of each pyramid using the formula for the volume of a pyramid:
\[ V = \frac{1}{3}Bh \]
where \( V \) is the volume, \( B \) is the area of the base, and \( h \) is the height.
First, let's calculate the volume of pyramid A:
\[ \text{Area of base of pyramid A} = \text{length} \times \text{width} = 10 \, \text{meters} \times 20 \, \text{meters} = 200 \, \text{square meters} \]
Now, let's call the height of pyramid A (and originally pyramid B) \( h \). Then, the volume of pyramid A is:
\[ V_{\text{A}} = \frac{1}{3} \times 200 \, \text{m}^2 \times h = \frac{200h}{3} \, \text{cubic meters} \]
Next, let's calculate the volume of pyramid B with its original height \( h \):
\[ \text{Area of base of pyramid B} = \text{side} \times \text{side} = 10 \, \text{meters} \times 10 \, \text{meters} = 100 \, \text{square meters} \]
So the original volume of pyramid B is:
\[ V_{\text{B}} = \frac{1}{3} \times 100 \, \text{m}^2 \times h = \frac{100h}{3} \, \text{cubic meters} \]
Now we can compare the volumes of pyramid A and the original volume of pyramid B:
\[ \frac{V_{\text{A}}}{V_{\text{B}}} = \frac{\frac{200h}{3}}{\frac{100h}{3}} = \frac{200}{100} = 2 \]
So, pyramid A has twice the volume of pyramid B.
Now, if the height of pyramid B increases to twice that of pyramid A, its new height is \( 2h \). Therefore, the new volume of pyramid B is:
\[ V_{\text{B new}} = \frac{1}{3} \times 100 \, \text{m}^2 \times 2h = \frac{200h}{3} \, \text{cubic meters} \]
Comparing this new volume of pyramid B to the volume of pyramid A:
\[ \frac{V_{\text{B new}}}{V_{\text{A}}} = \frac{\frac{200h}{3}}{\frac{200h}{3}} = 1 \]
So, the new volume of pyramid B is equal to the volume of pyramid A.
In summary, the volume of pyramid A is twice the volume of pyramid B when their heights are the same. If the height of pyramid B increases to twice that of pyramid A, the new volume of pyramid B is equal to the volume of pyramid A.

What is the ratio of 102 steps walked in 1 minute?

Answers

Answer:

102 steps/1minute

In seconds it would be 102/60 which can be reduced to 17/10, or 1.7

Help please and fast

Answers

Answer:

b. 7/16

Step-by-step explanation:

We can see in the figure that the total dimension parallel to C is 15/16.

The other half dimension with c is 1/2

We will get the dimension C by subtracting 1/2 from 15/16

So,

C = 15/16 - 1/2

= (15-8)/16

=7/16

So the dimension C is 7/16.

Hence option b is correct ..

The length of a rectangle is three times its width, and its area is 9 cm2

. Find the

dimensions of the rectangle.​

Answers

Answer:

3√3 cm. = l

√3 cm. = w

Step-by-step explanation:

l = 3w

9 = 3w[w] ↷

9 = 3w² [Divide by 3]

3 = w² [Take the square root]

√3 = w [plug this back into the top equation to get a length of 3√3 cm.]

I am joyous to assist you anytime.

Two lines and a transversal form corresponding angles that are congruent. Describe the two lines

Answers

Answer:

parallel

Step-by-step explanation:

If you have two lines and a transversal that form corresponding angles that are congruent. Then the alternate interior angles are congruent and the same-side interior (some people call these consecutive angles) are supplementary.

This has to deal with Parallel Lines Theorem or the Converse of Parallel Lines Theorem.

The lines would be parallel.

Two lines will be parallel.

What is corresponding angle?

When two lines are cut by a transversal then the angles formed relatively same position in their respective line at the intersection transversal and two lines are called corresponding angles.

What is converse of corresponding angles theorem?

Converse of corresponding angles theorem states that When two lines are cut by a transversal and the formed corresponding angles are congruent then the two lines will be parallel.

Here given that two lines and transversal are forming corresponding angles which are congruent. So by converse of corresponding angles theorem, the two lines will be parallel to each other.

Therefore two lines will be parallel.

Learn more about corresponding angle

here: https://brainly.com/question/2496440

#SPJ2

m2 - 36 = 0

Several solutions please

Answers

Answer:

m = ±6

Step-by-step explanation:

m^2 -36 =0

Add 36 to each side

m^2-36 +36 = 0+36

m^2 = 36

Take the square root of each side

sqrt(m^2) = ±sqrt(36)

m = ±6

Answer:+6 or -6

Step-by-step explanation:m^2 - 6^2

it becomes difference of two squares,

(m+6) (m-6)=0

m-6=0,m=6

m+6=0,m=-6

A toy plush weighed one- sixth of a pound. A flimsy box can hold 4 pounds. How many toy plushes could the box hold?

Answers

Answer:

24 plushies

Step-by-step explanation:

1 pound = 6 toy plushies

6(4)=24

Given the function f(x)=-5x^2-x+20 find f(3)

Answers

Answer:

-28

Step-by-step explanation:

-5(3)^2 - 3 + 20

-5*9 - 3 + 20

-45 -3+ 20

-48+ 20

-28

Hope it helps!

helppppppppppppppppppppping

Answers

Answer:

B

Step-by-step explanation:

First we simplify the equation:

3y − 2x = k (5x − 4) + 6

3y − 2x = 5k x − 4k + 6

3y = (5k + 2) x − 4k + 6

y = (5k + 2)/3 x + (6 − 4k)/3

The line has a positive slope and negative y-intercept.  So:

(5k + 2)/3 > 0

(6 − 4k)/3 < 0

Solving for k in each:

k > -2/5

k > 3/2

k must be greater than -2/5 and 3/2.  Since 3/2 is already greater than -2/5, then k must be greater than 3/2.

If k > 3/2, then it's also true that k > 0.  So the answer is B.

What is 80% of 80 round to the nearest hundreds

Answers

512,000 80 times 100 times 80 times .8

Answer:64

Step-by-step explanation:

Nat bought 3 colas for $1.25 each, 2 hot-dogs for $2.50 each, and a hamburger for $6.50. He paid with $20 bill. How much money does Nat have left?

Answers

Answer:

$4.75 is how much money is left over

Step-by-step explanation:

3* 1.25= 3.75

2* 2.50= 5.00

1* 6.50+ 6.50

5.00+3.75+6.50= 15.25

20- 15.25= 4.75

Final answer:

Nat spent a total of $15.25 on colas, hot dogs, and a hamburger. After paying with a $20 bill, he has $4.75 left.

Explanation:

To calculate how much money Nat has left after his purchases, we will add up the cost of the items he bought and subtract that total from the $20 bill he used for payment.

Cost of 3 colas: 3 × $1.25 each = $3.75

Cost of 2 hot-dogs: 2 × $2.50 each = $5.00

Cost of 1 hamburger: $6.50

Now we'll sum these amounts to find the total spending:

Total spending = $3.75 + $5.00 + $6.50 = $15.25

Next, we subtract the total spending from the $20 bill:

Change = $20.00 - $15.25 = $4.75

Therefore, Nat has $4.75 left after his purchase.

The apother is 4 m and a side is 5.8 m. What is the area
of the pentagon? Round to the nearest whole number.

Answers

Answer:

58 m^2.

Step-by-step explanation:

The  area of one of the 5 triangles is:

1/2 * 5.8 * 4 = 11.6 m^2

So the area of the pentagon

= 5 + 11.6

= 58 m^2

Answer:

The area is 58 meters squared.

Step-by-step explanation:

Since the pentagon is conveniently split into 5 separate but equal triangles, we only need to find the area of 1 triangle to find the rest. The area of triangles, as I'm sure you know, is 1/2bh. Using this equation, we get (1/2)x4x5.8. This equals 11.6. This is the area of one of the triangles. There are 5 triangles, so we multiply the area of 1 triangle by 5. 11.6x5= 58 meters squared. Hope this helped. :)

A = B/2 = C/5 a:b:c=?

Answers

Answer:

[tex]\large\boxed{A:B:C=\dfrac{1}{10A}}[/tex]

Step-by-step explanation:

[tex]A=\dfrac{B}{2}=\dfrac{C}{5}\\\\A=\dfrac{B}{2}\qquad\text{multiply both sides by 2}\\\\2A=B\to\boxed{B=2A}\\\\A=\dfrac{C}{5}\qquad\text{multiply both sides by 5}\\\\5A=C\to C=5A\\\\A:B:C=A:2A:5A=1:2:5A=\dfrac{1}{2}:5A=\dfrac{1}{2}\cdot\dfrac{1}{5A}=\dfrac{1}{10A}[/tex]


55. If 3x = 4y, the value of (x + y)^2 : (x - y)^2 is:

Answers

Answer:

[tex]\large\boxed{(x+y)^2:(x-y)^2=49}[/tex]

Step-by-step explanation:

[tex]3x=4y\qquad\text{subtract}\ 3y\ \text{from both sides}\\\\3x-3y=y\qquad\text{distributive}\\\\3(x-y)=y\qquad\text{divide both sides by 3}\\\\x-y=\dfrac{y}{3}\qquad(*)\\------------------\\3x=4y\qquad\text{add}\ 3y\ \text{to both sides}\\\\3x+3y=7y\qquad\text{distributive}\\\\3(x+y)=7y\qquad\text{divide both sides by 3}\\\\x+y=\dfrac{7y}{3}\qquad(**)\\------------------[/tex]

[tex](x+y)^2:(x-y)^2=\dfrac{(x+y)^2}{(x-y)^2}\qquad\text{use}\ \left(\dfrac{a}{b}\right)^n=\dfrac{a^n}{b^n}\\\\=\left(\dfrac{x+y}{x-y}\right)^2\qquad\text{substitute}\ (*)\ \text{and}\ (**)\\\\=\left(\dfrac{\frac{7y}{3}}{\frac{y}{3}}\right)^2=\left(\dfrac{7y}{3}\cdot\dfrac{3}{y}\right)^2\qquad\text{cancel}\ 3\ \text{and}\ y\\\\=(7)^2=49[/tex]

what is the solution to x=√3x+10?

Answers

Answer:

x=5

Step-by-step explanation:

Given

[tex]x=\sqrt{3x+10}[/tex]

Squaring on both sides

[tex]x^2=(\sqrt{3x+10})^2 \\x^2=3x+10\\x^2-3x-10 = 0\\x^2-5x+2x-10 = 0\\x(x-5)+2(x-5) = 0\\(x-5)(x+2)=0\\x=5\\and\\x=-2[/tex]

Since putting -2 gives us:

[tex]-2=\sqrt{3(-2)+10} \\-2=\sqrt{-6+10}\\-2=\sqrt{4}\\-2\neq 2[/tex]

2 is an extraneous solution.

Therefore, the solution to x=√3x+10 is x=5 ..

$1334 is deposited into a savings account at 8% interest, compounded quarterly. To the nearest year, how long will it take for the account balance to reach $1,000,000?

Answers

Answer:

  84 years

Step-by-step explanation:

The future value of an investment is given by ...

  FV = P(1 +r/n)^(nt)

where P is the principal amount, r is the annual rate, and n is the number of times per year interest is compounded. Filling in the given values and solving for t, we get ...

  1000000 = 1334(1 +.08/4)^(4t)

  749.6252 ≈ 1.02^(4t) . . . . divide by 1334 and simplify

  log(749.6252) ≈ 4t·log(1.02) . . . . take logarithms

  t ≈ log(749.6252)/(4·log(1.02)) ≈ 83.57

It will take about 84 years for the account balance to reach $1,000,000.

Other Questions
A serving fish contains 50 g of protein and 4 gof fat. If protein has a caloric calue of 4.0 kcal/g and fat has 9.1 kcal/g, how many kcal are in the serving? Fill in the blank.if necessary, use the slash marks (/) for a function bar. if sin theta= 3/5, then cos theta= analyze the numberline below and answer the question that follows. where could point e be if bc=de and d is between e and b? Find the equation of a line given the point and slope below. Arrange your answer in the form y = mx + b, where b is the constant.(1, 3)m = 3i need help with this question and others like it, an explanation would be great, im on a deadline and need to finish these as soon as possible ty Why did English settlers colonize New England in the mid-1600s? Which of the following airways precisely carry air to each of the lung?a. terminal bronchiolesb. bronchiolesc. tertiary bronchid. secondary bronchie. primary bronchi How many electrons does a single oxygen gain or lose in the following reaction?H 2 + O 2 H 2 O The primary stress on one syllable of a word is called the ___? Which numbers are imaginary numbers ? Bernard solved the equation 5x+(-4)=6x+4 using algebra tiles.Which explains why Bernard added 5 negative x-tiles to both sides in the first step of the solution ? Two trains leave towns 1152km apart at the same time and travel toward each other. One train travels 14km/h slower than the other. If they meet in 4 hours, what is the rate of each train? Does this sound right for a thesis statement? "Martin Luther King, Jr. used stylistic elements such as the use of simile, imagery, metaphor, and other rhetorical devices, these stylistic elements helped King to influence the person reading the letter, these elements help persuade those reading this letter to see where Martin Luther King Jr. is coming from factually and emotionally." Cognitive-behavioral techniques: a. may substitute for drug treatments in case of severe hypertension. b. can be used without supervision and have no side effects. c. are expensive and highly difficult to implement. d. have been moderately successful in the treatment of hypertension. If there were no air resistance, a penny dropped from the top of a skyscraper would reach the ground 9.3 s later. To the nearest integer, what would the penny's speed in m/s be right as it reaches the ground if it was dropped from rest? Find all solutions to the equation sin(3x)cosx+sinx cos(3x)=0 on the interval [0,2pi]a- x=0,pi/4,pi/2,3pi/4,pi,3pi/2,2pib- x=0,pi/2,pi,3pi/2,2pic- x=0,pi,2pid- x=0,pi/2,3pi/2 Is the Illinois conceal carry law consistent with the social contract theory What is the total number of common tangents that can be drawn to the circles?A. 0B. 2C. 1D. 3 How would you do this problem? It gives me the right answer but I need to show my work. Which of the following statement(s) about cells is/are true?1. Mitosis --- division of somatic cells 2. Meiosis --- division of sex cells 3. Somatic cells are diploid 4. Sex cells are haploid A) 1, 2, 3, 4 B) 1 and 2 C) 3 and 4 D) 1 and 4 E) 1, 2 and 4 In a nuclear reactor, more fuel is burned than is consumed. a)-True b)- False